ضوابط اللإختيار والتعيين في العصرين اللأموي والعباسي: Control and Selection Controls in the Umayyad and Abbasid Periods - Masoud, Riham. S.; Asmuliadi bin Lubis,; Nordin, Kamaruzzaman (Journal Al-Muqaddimah, 2020)
The selection and appointment process during recruitment has evolved throughout the Islamic ages in terms of controls and principles that are based on by the state because the selection and appointment process works to achieve the goals of the institution or organization, as this study aimed to introduce the selection and appointment controls in the Umayyad and Abbasid era, as these two eras are The most important Islamic eras that took care of this aspect, and most of these points will be addressed by identifying the most important caliphs who were interested in the selection and appointment process, and through the descriptive historical analytical method we try to reach the most important points that highlight the selection process The appointment is in accordance with the Islamic regulations that must be followed during the recruitment process. The result concluded that the Umayyad and Abbasid eras provided us with an advanced understanding of the criteria for selection and appointment based on merit and competence.